Postprandial expression of growth-related genes in Atlantic salmon (Salmo salar L.) juveniles fasted for 1 week and fed a single meal to satiation - Valente, Luisa M. P.; Bower, Neil I.; Johnston, Ian A. (British Journal of Nutrition, 2012)
We investigated postprandial changes in transcript abundance following a single satiating meal in juvenile Atlantic salmon (Salmo salar L.) (about 70 g body mass) following fasting for 1 week at 12 degrees C. The expression of twenty-three growth-related genes was determined in fast myotomal muscle using quantitative real-time PCR at the following postprandial time points: -12, 0, 1, 3, 6, 12, 24, 48 and 96 h. The gut was fullest 1-6 h after feeding and emptied within 48-96 h. IGF-I, MyoD1c, MRF4 and myf5 transcripts were sharply up-regulated within 1 h of refeeding and are promising candidate genes involved in a fast-response signalling system that regulates fish myotomal muscle growth. These genes clustered together with MyoD1b and suggest a coordinated regulation to favour resumption of myogenesis as an early response to feeding. Insulin-like growth factor (IGF)-II and the ubiquitin ligase MAFbx/atrogin-1 were initially down-regulated but restored to initial values after 12 h. It is also suggested that local production of IGF-I within the muscle might suppress catabolic pathways depressing MAFbx/atrogin-1.